E-KINERJA PEGAWAI MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (STUDI KASUS KLINIK ANDIKA) - Fahreza, Ganang Yudha; Hasdiana; Andriana, Septiana Dewi (Cattleya Darmaya Fortuna, 2025)
Andhika Clinic must have a relevant strategy according to the characteristics of its services, a strategy that can be implemented, the service is better, when compared to what its competitors are doing. So Andhika Clinic must maintain service to patients. Good employee performance is measured by patient satisfaction in receiving the services provided by employees. And this service will maintain patient loyalty for treatment at Andhika Clinic. Employee performance appraisal is influenced by several factors. These factors can result in service procedures not being carried out in accordance with applicable regulations and when sending patient complaints they still use a suggestion box, making it very difficult to convey patient complaints directly in the performance of employees in serving patients. Using the Importance Performance Analysis (IPA) method to overcome the above problems in terms of addressing service quality which affects employee performance by designing a website-based application. The advantage of the Importance Performance Analysis (IPA) method is that it can show attributes that need to be improved or reduced to maintain patient satisfaction.